Biological control of Bemisia argentifolii (Homoptera: Aleyrodidae) on poinsettia with inundative releases of Encarsia formosa (Hymenoptera: Aphelinidae): are higher release rates necessarily better? - Hoddle, M; Van Driesche, R; Sanderson, J (Biological control, 1997)
The effectiveness of inundative releases of the parasitoid Encarsia formosa for control of Bemisia argentifolii on poinsettia was determined in replicated experimental greenhouses. We evaluated two release rates of E. formosa: a low release rate (1 wasp/plant/week, released in two greenhouses, in spring 1995) and a high release rate (3 wasps/plant/week, released in two green-houses, in fall 1993), each over a 14-week growing season. Each release trial had one or two control greenhouses in which B. argentifolii developed on poinsettia in the absence of E. formosa. Life-tables were constructed for B. argentifolii in the presence and absence of E. formosa by using a photographic technique to follow cohorts of whiteflies on poinsettia leaves. Weekly population counts of the whitefly were also made. In the absence of E. formosa, egg to adult survivorship of B. argentifolii on poinsettia was 75-81%. At the low release rate, egg to survivorship of B. argentifolii was 5% and parasitism was 13%. At the high release rate, egg to adult survivorship for B. argentifolii was 8% and parasitism was 23%. The net reproductive rates (R0) for B. argentifolii populations in the absence of E. formosa ranged from 18.01-26.12, indicating a rapidly increasing population. Net reproductive rates for whitefly populations subject to wasp releases were 1.54 for the low release rate greenhouses and 2.11 for the high release rate greenhouses, indicating substantially reduced B. argentifolii population growth. The low release rate provided better control of B. argentifolii than the high release rate. This difference was attributed to higher levels of mortality of whiteflies at the low release rate in the first 5-6 weeks of the growing period. We suggest that mutual interference may also have affected observed levels of mortality and parasitism